Cartographier la science-fiction au théâtre - Romain Bionda (ReS Futurae)
Science-fictional elements are present on the western stages of the 20th and 21st centuries: science-fiction takes several forms and assumes various functions. To facilitate its study, these pages aim at clarifying the data of the problem (still rarely faced) by proposing historical, historiographical, and theoretical references. Numerous examples of shows are presented - from theater, dance, opera, and performance - in order to try to grasp the phenomenon in its complexity. This paper introduces the issue entitled “Le théâtre de science-fiction : premiers éléments de cartographie”.